The simulation and the optimization of the quality function of the process of the nanoscale film’s growth - V. A. Tupik; T. Su. Chu; I. Steblevska (Известия высших учебных заведений России: Радиоэлектроника)
The modeling of processes of formation of thin films in magnetron sputtering systems in the substrate potential field at different ratios of relations between the sprayed material and the substrate for various types of structures of the substrate is considered. Growth models of thin films point emitters integration method with the use of Monte-Carlo algorithms with accounting of the annealing are used. The comparison of results of computer simulation and experiment is executed; the inverse problem to optimization process using the quality function that takes into account the uniformity of the synthesized thin films, the flow of materials and the geometry of the spray is solved.